THE ANALYSIS OF THE ILLOCUTIONARY ACTS IN THERESA MAY’S BRITAIN, THE GREAT MERITOCRACY SPEECH - Puteri, Maharani Saskia; Arifin, M. Bahri; Sanhadi R., Famala Eka (Fakultas Ilmu Budaya Universitas Mulawarman, 2020)
Political leaders used political speech that contained intentional purposes to suggest various political agenda. Theresa May, United Kingdom’s prime minister from 2016 to 2019, used political speech entitled Britain, the great meritocracy to deliver British exit (Brexit). Therefore, to discover the purposes of May’s speech, this study aimed to identify the types of illocutionary acts employed in the speech based on Searle’s theory of the classification of illocutionary acts and the contexts underlying the illocutionary acts produced based on Hymes’ SPEAKING model of contexts. To conduct this study, descriptive-qualitative method and content analysis approach were used. Then, the data collection was done by close reading, speech listening, and note taking techniques. After that, compiling, disassembling, reassembling, interpreting and concluding were taken as data analysis process. Finally, the results of the study showed that 4 (four) illocutionary act types namely assertives, directives, commissives, and expressives were employed in the speech. By these findings, assertive type was the most frequently used one as this type enabled the speaker to characterize her belief to be in true or false dimensions. Functionally, it transmitted the prominent purpose of the speech which was to show both preferences and disfavors of May upon Britain. Otherwise, declaration type was not found to fit in the specific context presented at that time that was to depict how Britain should be within May’s term. Additionally, contexts underlying the emergence of the illocutionary acts in the speech were setting and scene, participants, ends, act sequence, key, instrumentalities, norms, and genre.